PERBANDINGAN LOYALITAS PEMILIH ABANGAN DAN SANTRI TERHADAP KHOFIFAH DAN SAIFULLAH YUSUF PADA PEMILIHAN GUBERNUR JAWA TIMUR TAHUN 2018 - Novy Setia Yunas; Baiqun Isbahi (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This paper will review the comparison of loyalty of Abangan and Santri voters to two contestants in East Java Pilgub 2018. The reason, East Java Pilgub 2018 was followed by two contestants who both came from Nahdlatul Ulama. But on the other hand, political contestation in East Java cannot be separated from the cultural political dynamics scattered in the four corners of Mataraman, Tapal Kuda, Arek and Madura. These four regions certainly have the characteristics and loyalty of different voters both politically and sociologically. The political map certainly cannot be separated from Clifford Geertz classical study of the typology of the “aliran” politics (politik aliran) in Java. The method used in this paper is Library Research. The main information in this study was obtained through the analysis of the publication of the results of Kompas R&D survey in February and May 2018. The result of comparison analysis of loyalty of voters will not only know the extent of loyalty support of cultural groups on both candidates but see the tendency of reorientation of voting behavior in each cultural group from the influence of cadence and culture shifted to the orientation of the issues brought by the candidate.